Moral hazard in high-risk environments: optimal follow-on investing in venture capital finance. Issue 4 (2nd October 2018) - Tennert, Julius; Lambert, Marie; Burghof, Hans-Peter
ABSTRACT: This paper examines the joint effect of environmental risk and moral hazard on staging activity in venture capital financing. We show theoretically and empirically that venture capitalists face a trade-off between (a) deferring and staging investments to engage in learning of the risky venture and avoid downside losses and (b) committing additional funds to update the incentive of the entrepreneur. We describe this trade-off through the timing of follow-on investments and show that highly qualified entrepreneurs demand greater compensation (a larger share) than do less-qualified entrepreneurs in situations of high risk.